2002
DOI: 10.1161/hs0102.100533
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Early Admission in a French Stroke Unit

Abstract: Background and Purpose-Intravenous tissue plasminogen activator improves outcome after ischemic stroke when given within 3 hours of symptoms onset in carefully selected patients. However, only a small proportion of acute stroke patients are currently eligible for thrombolysis, mainly because of excessive delay to hospital presentation. We sought to determine the factors associated with early admission in a French stroke unit. Methods-We prospectively studied the admission delay of acute stroke patients in a Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

33
153
8
14

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(208 citation statements)
references
References 35 publications
33
153
8
14
Order By: Relevance
“…This study showed that arriving at hospital was delayed for elderly people living alone and patients without access to outside help at the onset of symptoms. These findings are similar to previous results: that recognition of symptoms by bystanders facilitated an early arrival at hospital (Derex et al, 2002;Rosamond et al, 1998); and elderly people living alone, patients without access to outside help, and patients who do not maintain contact with others experience a delayed arrival at hospital (Wester et al, 1999). Hence, the difficulties experienced by many stroke patients in taking quick and appropriate action by themselves makes it necessary to comprehensively educate families, friends, neighbors, and community as well as the patients themselves.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study showed that arriving at hospital was delayed for elderly people living alone and patients without access to outside help at the onset of symptoms. These findings are similar to previous results: that recognition of symptoms by bystanders facilitated an early arrival at hospital (Derex et al, 2002;Rosamond et al, 1998); and elderly people living alone, patients without access to outside help, and patients who do not maintain contact with others experience a delayed arrival at hospital (Wester et al, 1999). Hence, the difficulties experienced by many stroke patients in taking quick and appropriate action by themselves makes it necessary to comprehensively educate families, friends, neighbors, and community as well as the patients themselves.…”
Section: Discussionsupporting
confidence: 92%
“…A sudden onset of stroke, rapidly progressing symptoms, and continuous symptoms resulted in a higher seriousness of symptoms. These findings are similar to those other studies: a higher NIHSS (National Institutes of Health Stroke Scale Score) (Derex et al, 2002;Chang et al, 2004;Bohannon, Silverman, & Ahlquist, 2003) and more severe neurological symptoms when arriving at hospital (Wester et al, 1999;Goldstein, Edwards, & Wood, 2001;Wang et al, 2002) facilitated an earlier arrival at hospital.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The American College of Cardiology and the American Heart Association guidelines for the management of ST-elevation myocardial infarction state that percutaneous coronary intervention should be performed as quickly as possible, preferably within 90 minutes from the moment of first medical contact. 18 Although there are similarities between stroke and myocardial infarction treatment, procedure times in stroke have much larger variations due to considerable variability in tortuosity, vessel location, and the nature of the occlusion. 14,16 Such variability in procedure time in patients with acute stroke, unlike those with myocardial infarction, increases the likelihood of a prominent relationship to outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Because the majority of acute serious medical emergencies take place in residential locations, any additional time it takes to reach patients is particularly important in locales with a high concentration of apartment buildings. [2][3][4][5] Several other studies have reported on-scene to patient time intervals. [6][7][8][9] In a study of four EMS regions in Arizona, the on-scene to patient interval was 1.0 minute.…”
Section: Discussionmentioning
confidence: 99%